2022
DOI: 10.3390/nano12203577
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation of Fast Neutron and Gamma Radiation Properties of Polycarbonate-Bismuth Oxide Composites Using Geant4

Abstract: The gamma mass (µm) and linear (µ) attenuation coefficients of polycarbonate-bismuth oxide composites (PC-Bi2O3) with different bismuth oxide weight factors were investigated theoretically using EpiXS and a Monte Carlo simulation-based toolkit and Geant4 within an energy range between 0.1 and 2 MeV. The wide energy ranges of gamma rays and neutrons were chosen to cover as many applications as possible. The attenuation coefficients were then used to compute the half-value layers. The effective atomic numbers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In this context, many parameters (Mass Attenuation Coefficient (MAC), Linear Attenuation Coefficient (LAC), Half Value Layer (HVL), Mean Free Path (MFP), Atomic Cross-Sections, Total Electronic Cross-Sections, Effective Atomic Number (Z eff ), Effective Electron Density (N eff ), Effective Conductivity (C eff ), Fast Neutron Removal Cross-Section (FNRCS), Exposure Build-up Factor (EBF), and Energy Absorption Build-up Factor (EABF)) are used to test the radiation absorption performance of the NCs formed, and all these parameters used in the study are presented in table 1 [56][57][58][59][60][61][62][63][64].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, many parameters (Mass Attenuation Coefficient (MAC), Linear Attenuation Coefficient (LAC), Half Value Layer (HVL), Mean Free Path (MFP), Atomic Cross-Sections, Total Electronic Cross-Sections, Effective Atomic Number (Z eff ), Effective Electron Density (N eff ), Effective Conductivity (C eff ), Fast Neutron Removal Cross-Section (FNRCS), Exposure Build-up Factor (EBF), and Energy Absorption Build-up Factor (EABF)) are used to test the radiation absorption performance of the NCs formed, and all these parameters used in the study are presented in table 1 [56][57][58][59][60][61][62][63][64].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Phy-X/PSD is a program that calculates the photon cross-sections and energy deposition in materials [56][57][58], while EpiXS is a Monte Carlo simulation program that can accurately predict radiation transport and energy deposition in complex geometries [59][60][61][62][63]. XMuDAT is a software package for calculating attenuation coefficients and cross-sections for various materials [19,46,[64][65][66].…”
Section: Introductionmentioning
confidence: 99%
“…Much of this research demonstrated that polymers' photon attenuation capabilities are promising, and their capacity to attenuate photons be boosted by combining them with various composites with high atomic numbers. Numerous investigated polymers also have high thermal neutron cross-sections and high neutron particle sensitivity, making them excellent neutron-shielding materials [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum, iron oxide, aluminum, zinc oxide, and titanium dioxide comp chosen as the most significant composites that have outstanding impacts on shielding properties. Silver and gold composites also have a good impact on properties, but it is well known that silver and gold composites are expensive; experimental studies of their effects are limited, and a better approach is to use to examine the properties of a substance doped with silver or gold composite In this work, photon and neutron attenuation properties of Polyimide different weights fractions of those mentioned composites (5,10,15,20,25 wt.% energy range (from 10 to 2000) keV have been theoretically investigated u Carlo simulation.…”
Section: Introductionmentioning
confidence: 99%
“…EpiXS was produced for photon attenuation, dosimetry, and shielding, which covers a broad energy range 1 keV-1 GeV. EpiXS has been a code widely preferred by researchers lately [19,[23][24][25][26]. The XCOM software [27] was developed in order to estimate MAC values or photon interaction cross-sections of a single element, compound, or composite mixture in a wide energy region of 1 keV-100 GeV.…”
Section: Introductionmentioning
confidence: 99%